Driver beliefs regarding the benefits of reduced speeds. Issue 4 (2nd October 2017) - Debnath, Ashim Kumar; Haworth, Narelle; Rakotonirainy, Andry
ABSTRACT: Despite many studies of the benefits of reducing driving speeds for safety, vehicular emissions, and stress in driving, little is known regarding how drivers perceive these benefits and the factors influencing their beliefs. This article examines the factors influencing driver perceptions of the benefits attainable by reducing travel speeds. Driver perceptions of the extent to which reducing speed would lead to improved safety, lower emissions, and reduced stress and road rage were collected in an online survey of 3, 538 drivers in Queensland, Australia. An analysis using seemingly unrelated regression showed that drivers of automatic cars and bicycle commuters more strongly agreed that lower speeds would provide these benefits than other drivers, whereas drivers who used premium fuel thought otherwise. Users of ethanol-blended fuel believed more strongly that reductions in speeds would reduce emissions. Young drivers less strongly agreed regarding emissions and stress than older drivers. Females, drivers of small cars, and those who drive frequently with passengers agreed more strongly that speed reductions would improve safety and reduce stress and road rage. These findings indicate a need to develop targeted educational and training programs to help drivers better understand these benefits to improve their willingness to reduce speeds.